Black soldier flies as a latent driver to attaining selected SDGs in a developing country context- the case of Uganda - Junior Senyonga Kasima; Basil Mugonola; Emmanuel Menya; Sulaiman Ndaula; Elly Kurobuza Ndyomugyenyi (Sustainable Environment)
In developing countries, minimal progress has been made towards the attainment of Sustainable Development Goals (SDGs). This is because of low investment in innovations towards this endeavor. In this paper, 143 peer-reviewed journal articles and non-journal sources were reviewed to explore the potential of Black Soldier Fly (BSF) rearing as a cost-effective innovation for achieving SDGs 1, 2, 3, 7, and 13. Uganda was chosen for its median position among developing countries, making its practices adaptable to countries on either side of the scale. BSF can contribute to the attainment of the five SDGs through its products and/or services, including environment-friendly waste management, larvae for animal feeds, frass for organic fertilizer, and chitin for pharmaceutical use. This review discusses the significant potential of integrating BSF into strategies to achieve the selected SDGs in a developing country. However, the limited data on organic waste generation could not permit precise statistical estimates of BSF’s potential contribution to each SDG. Future studies, supported by reliable data, should precisely assess the feasibility of BSF rearing as a cost-effective innovation for attaining the SDGs. Future research should also explore the influence of policy and consumer behavior on the adoption and utilization of BSF-based products.